2011
DOI: 10.1103/physrevlett.107.167401
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfine Interaction-Dominated Dynamics of Nuclear Spins in Self-Assembled InGaAs Quantum Dots

Abstract: We measure the dynamics of nuclear spins in a self-assembled quantum dot at a magnetic field of 5 Tesla and identify two distinct mechanisms responsible for the decay of the Overhauser field. We attribute a temperature-independent decay which lasts ∼ 100 seconds to intra-dot diffusion induced by hyperfine-mediated indirect nuclear spin interaction. In addition, we observe a gate-voltage and temperature dependent decay stemming from co-tunneling mediated nuclear spin flip processes. By adjusting the gate-voltag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 29 publications
4
68
1
Order By: Relevance
“…The presence of strain and hence strong quadrupole effects is one of the main reasons that DNP is possible in zero external magnetic field 21,33,36,61,67 , where nuclear polarization life-times in the dark of up to tens of seconds have been observed 36,61 . Remarkably, in magnetic fields of a few T, nuclear polarization in strained self-assembled dots survives as long as 30 hours 36,60,61 . On the contrary, if a QD is brought in contact with an unpolarized electron reservoir, as is often the case in charge-tunable devices, nuclear spins are depolarized in a few milliseconds 36 .…”
Section: Dynamic Nuclear Polarizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of strain and hence strong quadrupole effects is one of the main reasons that DNP is possible in zero external magnetic field 21,33,36,61,67 , where nuclear polarization life-times in the dark of up to tens of seconds have been observed 36,61 . Remarkably, in magnetic fields of a few T, nuclear polarization in strained self-assembled dots survives as long as 30 hours 36,60,61 . On the contrary, if a QD is brought in contact with an unpolarized electron reservoir, as is often the case in charge-tunable devices, nuclear spins are depolarized in a few milliseconds 36 .…”
Section: Dynamic Nuclear Polarizationmentioning
confidence: 99%
“…Nuclear spin depolarization can occur via flip-flops between interacting (neighboring) nuclei, giving rise to nuclear spin diffusion. However, in most QDs the nuclear Zeeman splitting matching required for such nuclear-nuclear flip-flops is not fulfilled owing to quadrupole interactions occurring mainly as a result of strain 13,19,60,[64][65][66] . Thus nuclear spin diffusion is typically suppressed in QDs 36,60,61,63 .…”
Section: Dynamic Nuclear Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum NCSHFI-mediated depolarization is seen to be on the order of an hour. 67,68 Just as in the NMR spectra, above B Q level where Zeeman regime takes over, the NCSFHI gradually becomes weaker. …”
Section: Nmr Spectramentioning
confidence: 99%
“…24,29 In the case that only an electron exists in the QD region, which can be realized after the X À emission, the contact term contributes dominantly to the nuclear spin depolarization, because it is much stronger than the other depolarization terms. Latta et al revealed that the resident electron causes the nuclear spin depolarization via the hyperfine-mediated indirect nuclear spin interaction and the cotunneling mediated nuclear spin flips.…”
Section: B Depolarization Process Measurementmentioning
confidence: 99%